Nastajanje dokumenta Nostra aetate = Creating of the Document Nostra aetate - Osredkar, Mari Jože (Edinost in dialog, 2021)
The document of the Second Vatican Council, on which the modern Catholic doc-trine of interreligious dialogue is based, Nostra aetate or Declaration on the Relation of the Church with Non-Christian Religions was being written from 1960 to 1965. Pope John XXIII entrusted the work to Cardinal Augustin Bea, S.J. The draft text of the document went through four revisions. The Council Fathers first wanted the text to be a supplementary fourth chapter to the document Decree on Ecumenism. Then they proposed it be a separate chapter in the document Lumen Gentium. In October 1965 they voted that the text, which in its beginnings spoke only of Jews, would finally define the relationship of the Church to non-Christian reli-gions and would become an independent council document.